Mortality risk factors in a Spanish cohort of oldest-old patients hospitalized with COVID-19 in an acute geriatric unit: the OCTA-COVID study - Lozano Montoya, Isabel; Quezada Feijoó, Dolores Maribel; Jaramillo Hidalgo, Javier; Garmendia Prieto, Blanca; Lisette Carrillo, Pamela; Gómez Pavón, Francisco Javier (My University, 2021)
Purpose To determine predictors of in-hospital mortality related to COVID-19 in oldest-old patients. Design Single-center observational study. Setting and participants Patients ¿ 75 years admitted to an Acute Geriatric Unit with COVID-19. Methods Data from hospital admission were retrieved from the electronic medical records: demographics, geriatric syndromes (delirium, falls, polypharmacy, functional and cognitive status) co-morbidities, previous treatments, clinical, laboratory, and radiographic characteristics. Cox proportional hazard models were used to evaluate in-hospital mortality. Results Three hundred patients were consecutively included (62.7% females, mean age of 86.3 ± 6.6 years). Barthel Index (BI) was < 60 in 127 patients (42.8%) and 126 (42.0%) had Charlson Index CI ¿ 3. Most patients (216; 72.7%) were frail (Clinical Frailty Scale ¿ 5) and 134 patients (45.1%) had dementia of some degree. The overall in-hospital mortality rate was 37%. The following factors were associated with higher in-hospital mortality in a multi-variant analysis: CURB-65 score = 3¿5 (HR 7.99, 95% CI 3.55¿19.96, p < 0.001), incident delirium (HR 1.72, 1.10¿2.70, p = 0.017) and dementia (HR 3.01, 95% CI 1.37¿6.705, p = 0.017). Protective factors were concurrent use of angiotensin-converting enzyme inhibitors (HR 0.42, 95% CI 0.25¿0.72, p = 0.002) or prescription of hydroxychloroquine (HC 0.37 95% CI 0.22¿0.62, p < 0.001) treatment during admission. Conclusions and implications Our findings suggest that recognition of geriatric syndromes together with the CURB-65 score may be useful tools to help clinicians establish the prognosis of oldest-old patients admitted to hospital with COVID-19. Keywords Covid-19 · SARS-COV-2 · Mortality · Older adults · Risk factors